Demographic studies in two villages in the Upernavik District. - Balslev Jørgensen, J.; Hansen, Keld; Østergaard Hansen, A. (Meddelelser om Grønland, 1978)
The present work was carried out as part of a major investigation into Human Adaptation under the IBP, International Biological Program. Other results of these investigations have been published in Meddelelser om Grønland (Volumes no. 202 .2, 203.1, 203 .2). Statens Lægevidenskabelige Forskningsråd (L 78/68 and 512-33/69) and Ministeriet for Grønland have provided the necessary economical support.